2010
DOI: 10.1534/genetics.109.113746
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Expression of Spo13 Alters M-Phase Progression and Nucleolar Localization of Cdc14 in Budding Yeast

Abstract: Spo13 is a key meiosis-specific regulator required for centromere cohesion and coorientation, and for progression through two nuclear divisions. We previously reported that it causes a G2/M arrest and may delay the transition from late anaphase to G1, when overexpressed in mitosis. Yet its mechanism of action has remained elusive. Here we show that Spo13, which is phosphorylated and stabilized at G2/M in a Cdk/Clb-dependent manner, acts at two stages during mitotic cell division. Spo13 provokes a G2/M arrest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…It means that the effect of Spo13 expression was more lethal as compared to Rec8 expression. Varela et al first reported that mitotic Spo13 expression altered cell cycle progression and was unable to exit anaphase with change in the cell morphology [27]. We also observed same morphological change (elongated cell) in Spo13 expression strain (Fig.…”
Section: Resultssupporting
confidence: 85%
“…It means that the effect of Spo13 expression was more lethal as compared to Rec8 expression. Varela et al first reported that mitotic Spo13 expression altered cell cycle progression and was unable to exit anaphase with change in the cell morphology [27]. We also observed same morphological change (elongated cell) in Spo13 expression strain (Fig.…”
Section: Resultssupporting
confidence: 85%
“…The exact role of Spo13 in cohesin protection is currently unclear. Interestingly, SPO13 overexpression blocks cohesin cleavage during mitosis ( Lee et al ., 2002 ; Shonn et al ., 2002 ; Varela et al ., 2010 ), suggesting that Spo13 may also influence cohesin cleavage in meiosis, but how it might do so remains unresolved. Although Spo13 was implicated in ensuring the proper pericentromeric localization of Sgo1 ( Kiburz et al ., 2005 ), other studies have found no difference in chromosomally associated Sgo1 ( Galander et al ., 2019 ; Lee et al ., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report on the establishment of a system enabling controllable expression of a meiosisspecific complex in mitosis. Similar approaches have been used previously to investigate different aspects of meiosis, such as HR repair and chromosome segregation [8][9][10][11][12] . We express components of the trimeric, meiosis-specific Red1, Hop1 and Mek1 complex (i.e., the RHM complex), and show that this complex can self-assemble even when expressed outside of its natural, physiological environment, i.e., in mitotically-dividing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Meiosis can thus be seen as an adaptation of the mitotic cell cycle. One approach to understand meiosis-specific mechanisms is via reconstitution in non-physiological environments, for example via in vitro biochemical reconstitutions (e.g., [2][3][4][5][6][7] ), or by expressing meiosis-specific factors in non-meiotic cells (e.g., [8][9][10][11][12] ).…”
Section: Introductionmentioning
confidence: 99%